En Pronominalization in French and the Structure of Nominal Expressions. (15th February 2013) - Ihsane, Tabea
Abstract : Abstract.  In this paper, I tackle the question of the syntactic source of the clitic en in French, debated in the literature since the late 1970s (Kayne 1977 and Milner 1978). The aim is not only to find out what en pronominalizes but also to provide an analysis of nominal expressions able to account for (i) the quantitative, partitive, and genitive examples discussed by Milner (1978) and for (ii) the fact that du / des NPs can be replaced by en in some contexts only. What I suggest to account for the issues raised by en pronominalization is that quantitative nominals and du / des NPs have a unified structure that takes notions like number, quantity, and count/mass into account and that du / des NPs belong to different categories—that is, that their left periphery is composed differently. The idea is that, in addition to PPs, en can replace different layers of a nominal structure with an articulated left periphery and a fine‐grained inflectional domain, in a cartographic spirit. The property underlying all uses of en could be their lack of referentiality, as observed by Gross (1973) for quantitative en .